2015
DOI: 10.1073/pnas.1522297113
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographically isolated CD63 + CD81 + extracellular vesicles from mesenchymal stromal cells rescue cognitive impairments after TBI

Abstract: Extracellular vesicles (EVs) secreted by cells present an attractive strategy for developing new therapies, but progress in the field is limited by several issues: The quality of the EVs varies with the type and physiological status of the producer cells; protocols used to isolate the EVs are difficult to scale up; and assays for efficacy are difficult to develop. In the present report, we have addressed these issues by using human mesenchymal stem/stromal cells (MSCs) that produce EVs when incubated in a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
325
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(345 citation statements)
references
References 51 publications
5
325
1
2
Order By: Relevance
“…These data suggest that exosomes not only cross the BBB, but also deliver functional cargo to trigger gene expression in specific recipient cell types in the brain. effect of MSC-derived exosomes has also been demonstrated by independent laboratories in the mouse subjected to stroke and TBI (114,115). Systemic administration of MSC-derived extracellular vesicles to ischemic mice markedly reduced motor coordination deficits and enhanced angiogenesis and neurogenesis, while treatment of TBI mice with human MSCderived extracellular vesicles substantially preserved spatial leaning ability (114,115).…”
Section: Hsc-exosomes and Therapiesmentioning
confidence: 86%
See 1 more Smart Citation
“…These data suggest that exosomes not only cross the BBB, but also deliver functional cargo to trigger gene expression in specific recipient cell types in the brain. effect of MSC-derived exosomes has also been demonstrated by independent laboratories in the mouse subjected to stroke and TBI (114,115). Systemic administration of MSC-derived extracellular vesicles to ischemic mice markedly reduced motor coordination deficits and enhanced angiogenesis and neurogenesis, while treatment of TBI mice with human MSCderived extracellular vesicles substantially preserved spatial leaning ability (114,115).…”
Section: Hsc-exosomes and Therapiesmentioning
confidence: 86%
“…Emerging data from independent laboratories indicate that exosomes released from MSCs provide therapeutic benefits in stroke and TBI by modulating the brain microenvironment (114)(115)(116)(117)(118)(119). Intravenous administration of MSC-derived exosomes to rats subjected to focal cerebral ischemia or TBI substantially improved neurological function by promoting neurovascular remodeling during stroke and TBI recovery (116, 117, 119).…”
Section: Msc-derived Exosomes and Therapiesmentioning
confidence: 99%
“…However, previous studies show that only a small proportion of transplanted MSCs actually survive and few MSCs differentiate into neural cells in injured brain tissues. It seems that the predominant mechanisms by which MSCs participate in brain remodeling and functional recovery are likely related to their secretion-based paracrine effect rather than a cell replacement effect [45,[175][176][177][178] ( Figure 2).…”
Section: Neuroprotective and Neurorestorative Processes In The Traumamentioning
confidence: 99%
“…Exosomes play an important role in intercellular communication and are promising therapeutic agents because their complex cargo of proteins and genetic materials has diverse biochemical potential to participate in multiple biochemical and cellular processes, an important attribute in the treatment of complex diseases with multiple secondary injury mechanisms involved [45]. The refinement of MSC therapy from a cell-based therapy to cell-free exosome-based therapy offers several advantages, as it eases the arduous task of preserving cell viability and function, storage, and delivery to patient [175][176][177][178]. Further exploring the mechanisms by which the secretion-based paracrine effect of MSCs participates in neurorestoration and functional recovery following TBI is an outstanding opportunity for research.…”
Section: Neuroprotective and Neurorestorative Processes In The Traumamentioning
confidence: 99%
“…Arslan et al (2013) showed that a single intravenous administration of exosomes was effective in enhancing cardiac function and geometry after myocardial infarction due to bioenergetics re-establishment (increased ATP production), oxidative stress reduction and prosurvival signaling activation (enhanced PI3K/Akt signaling) (Arslan et al, 2013 (Nakamura et al, 2015). In the nervous system, MSC derived exosomes have been evaluated in the treatment of neurological and neurodegenerative diseases; they have been shown to enhance angiogenesis and neurogenesis, reduce inflammation and improve spatial learning and sensorimotor function (Kim et al, 2016;Zhang et al, 2015).…”
Section: Hematopoietic Stem Cell Based Drugsmentioning
confidence: 99%